Penilaian Usability Sistem Gasurkes “Go Bumil” untuk Pencarian Ibu Hamil di Wilayah Kota Semarang - Undari Nurkalis; Kusworo Adi; Farid Agushybana (Jurnal Manajemen Kesehatan Indonesia, 2019)
The Gasurkes System "Go Bumil" is an application system developed to improve the search performance of pregnant women by village level maternal and child health surveillance officers in the Semarang City area. Usability evaluation on the "Go Bumil" application system needs to be done to find out the usefulness of the application system for users.This type of research uses a pre-experimental design in a single group. Data collection used the PSSUQ questionnaire (Post Study System Usability Questionnaire). The research subjects were 12 respondents from urban KIA gasurkes, 104 respondents to pregnant women and postpartum mothers. The object of research is the "Go Pregnancy" application. Data processing methods use descriptive analysis using a weighted average.The results of the usability evaluation of the "Go Bumil" application with respondents to KIA gaskes, pregnant and postpartum mothers as a whole were satisfied with the application system developed. The overall results of the overall assessment on kelurahan gas, pregnant women and postpartum mothers in the category of system usefulness = 6.02 (range values 6.00 - 6.99 state respondents agree), information quality = 5.99 (range of values 5, 00 - 5.99 states the respondent somewhat agrees), interface quality = 5.99 (range values 5,00 - 5,99 state respondents somewhat agree) and overall satisfaction = 6.01 (range values 6,00 - 6,99 state respondent agreed). Based on the evaluation of the system usefulness, information quality, interface quality and overall satisfaction categories, it can be concluded that the respondents were satisfied with the "Go Bumil" application.